Efektifkah Pendidikan Kesehatan Reproduksi Remaja oleh Teman Sebaya? Sebuah Kajian Literatur - Toni Indriawan; Tanjung Anitasari Indah Kusumaningrum (Nur Science Institute and Perkumpulan Keluarga Berencana Indonesia (PKBI) Semarang, 2021)
Background: Adolescence is a period of rapid growth and development both physically, psychologically and intellectually. Some of the health problems that can be experienced by adolescents, one of which is about risky behavior from premarital sex to HIV, factors that can cause adolescents to engage in risky sexual behavior include lack of education or knowledge and attitudes of adolescents about the importance of maintaining reproductive health. This literature review aims to determine the effect of providing adolescent reproductive health education by peers on knowledge and attitudes about adolescent reproductive health and HIV. Method: The articles used in this literature review is 5 articles with searches conducted through Google Schoolar, PubMed, and Garuda using the keywords 'adolescent reproductive health education', 'adolescent HIV health education', and health education by peers'. The inclusion criteria of this literature review are the articles used indexed by SINTA, Scopus, Scimago or having ISSN, Full text, published in 2011-2021, and using themethod quasi-experimental. The method used is to summarize the five selected journals, analyze, and draw conclusions. Results: The results in research journals show value < 0.05 and value = 0.0001 < which means that there is an effect of providing reproductive health education by peers on knowledge and attitudes about adolescent reproductive health and HIV. Conclusion: There is an influence of adolescent reproductive health education by peers on knowledge and attitudes about adolescent reproductive health and HIV. Suggestions for future research are expected to pay more attention to procedures and measurement of research results using health education methods by peer educators.